PRIMA: an Automated Tool for Android Releases Homologation Review - Barbosa, Heryck Michael Dos Santos; Lancellotta, Pedro Ivo Pereira; Santos, João Gabriel C.; Albuquerque, Abda Myrria De; Sousa, Janislley O De (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft); 2023: Anais Estendidos do XIV Congresso Brasileiro de Software: Teoria e PráticaDO - 10.5753/cbsoft_estendido.2023.231521, 2023)
Software testing is essential in maintaining the quality and integrity of technological products. This paper outlines the development of PRIMA, an automated tool based on a methodology that improves the Android Releases homologation review process. PRIMA reviews the test artifacts generated by Google tradefed tools using a set of predefined rules to validate the information contained in result artifacts. Real-world Security Maintenance Release (SMR) tests were conducted in our company, demonstrating the effectiveness of our tool in the Android release homologation process reducing almost 50 % of Android software release approval time.